If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27p = 4p + -15 Reorder the terms: 27p = -15 + 4p Solving 27p = -15 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 27p + -4p = -15 + 4p + -4p Combine like terms: 27p + -4p = 23p 23p = -15 + 4p + -4p Combine like terms: 4p + -4p = 0 23p = -15 + 0 23p = -15 Divide each side by '23'. p = -0.652173913 Simplifying p = -0.652173913
| 21-66=x | | (2e+5)=(3e-2) | | (x+8)(x+5)= | | 2x+40=5x-14 | | -4X+1=3 | | (5/9x+83) | | x^2=3x^3+20x+50 | | ay=2y+40 | | j=(20-4j) | | (-1x)/((0.01x^2+1)^2)=0 | | ((5/8a)+6)=(3/4a) | | ((1/4n)+10)=(2/3n) | | 5a+2=3a-5 | | 8x+5=54 | | (-1x)/(0.01x^2+1)^2 | | 8x+13=-18 | | (-1x)/(0.01x^2+1)^2=0 | | 170-4x=23x+20 | | 13-7x=61-21x | | (x+8)/(x+3)=0 | | 3j=20-4j | | 21-4y=-7 | | 14-7x=34-21x | | x^2+35x+60=0 | | 4x-2=-1+2x | | x^2-22x+32=0 | | 5x+1=2x | | 2x^2-1x=55 | | -2x+12=3x-16-x | | (2/3+12i)(1/6+24i) | | 7x-5=5x-4 | | (x^2+48)^1/2=8 |